SCREENING OF GENETIC MUTATION IN ABCA1 GENE AND RELATIONSHIP OF LOW-DENSITY LIPOPROTEIN AND TRIGLYCERIDES IN PATIENTS WITH TYPE 2 DIABETES WITH AND WITHOUT DYSLIPIDEMIA - Sarfraz, Munnaza; Rashid, Amir; Mustafa, Midhat; Khan, Saleem Ahmad; Majeed, Asifa (Pakistan Armed Forces Medical Journal, 2020)
Objective: To find the genetic mutation in exon-9 of the ABCA1 gene and relationship of serum low-density lipoprotein levels and serum triglycerides in patients with type 2 diabetes mellitus with and without dyslipidemia.Study Design: Cross-sectional comparative.Place and Duration of Study: Department of Biochemistry and Molecular Biology, Army Medical College Rawalpindi, from Jan to Dec 2017.Methodology: Ninety subjects were selected and divided into three groups, thirty in each. The division was based on newly diagnosed patients of type 2 diabetes with dyslipidemia, newly diagnosed patients of type 2 diabetes and healthy individuals. Genomic DNA was extracted from the blood samples of all subjects. Exon-9 of the ABCA1 gene was amplified through polymerase chain reaction and sequenced on automated DNA sequencer. The biochemical data was analyzed by SPSS-20 and presented in percentage and mean  SD.Results: The pattern of sequences of ABCA1 gene was found normal in patients of the group I and II through DNA sequencing. The levels of triglycerides were found elevated and mean value was 2.45 ± 0.57 for patients with diabetic dyslipidemia as compared to diabetic and control groups. The levels of low-density lipoproteins were observed as normal with mean value of 1.50 ± 0.22.Conclusion: The ABCA1 gene did not carry any genetic mutation in exon-9 in studied subjects. The raised level of triglyceride lipoproteins was a typical sign of dyslipidemia with a normal profile of low-density lipoproteins.